An improved synthesis of 4-cyano-1,10-phenanthroline, 4,7-dicyano-1,10- phenanthroline and their bis(4,4′-di-tert-butyl-2,2′-bipyridine) ruthenium(II) complexes - Staehle, Robert; Menzel, Roberto; Peuntinger, Katrin; Pilz, T. David; Heinemann, Frank Wilhelm; Guldi, Dirk Michael; Beckert, Rainer; Rau, Sven (Polyhedron, 2014)
This report describes a new palladium catalyzed synthesis of 4-cyano-1,10-phenanthroline (nphen, 1), 4,7-dicyano-1,10-phenanthroline (dnphen, 2) and their corresponding ruthenium complexes. The two cationic complexes, [(tbbpy)Ru(nphen)] 3 and [(tbbpy)Ru(dnphen) ] 4 (tbbpy = 4,4′-di-tert-butyl-2,2′-bipyridine), were synthesized using an improved microwave procedure. All compounds were fully characterized, including the solid-state molecular structures of the complexes. The influence of 1 and 2 on the metal-to-ligand charge transfer (MLCT) transitions were studied and compared to the ruthenium(II) polypyridyl complexes containing the related 4,4′-dicyano-2,2′-bipyridine (dnbpy) and the non-functionalized 1,10-phenanthroline (phen) ligand. © 2014 Elsevier Ltd. All rights reserved.

A study of acridine and acridinium-substituted bis(terpyridine)zinc(ii) and ruthenium(ii) complexes as photosensitizers for O2 ( 1Δg) generation - Eberhard, Jens; Peuntinger, Katrin; Rath, Susann; Neumann, Beate; Stammler, Hans-Georg; Guldi, Dirk Michael; Mattay, Jochen (Photochemical & Photobiological Sciences, 2014)
The homoleptic zinc(ii) and ruthenium(ii) metal complexes of bis(tridentate) 9-acridine and 10-methyl-9-acridinium-substituted terpyridines were tested for their suitability as triplet photosensitizers (PS) using the photooxidation of 1,5-dihydroxynaphthalene (DHN) to Juglone as a model reaction. Singlet oxygen (OΔ) generation is superior or comparable to Ru(bpy) for the acridine complexes, whereas the acridinium complexes are ineffective. The molecular structure of the bis(9-(5-([2,2′:6′,2′′-terpyridin]- 4′-yl)thien-2-yl)-10-methylacridinium)zinc(ii) complex ([Zn(MeATT) ][PF]) is determined by X-ray structure analysis, whereas for other complexes DFT calculations were performed for structural parameters to obtain insights into their electronic properties. This journal is © The Royal Society of Chemistry and Owner Societies.

Carbene based photochemical molecular assemblies for solar driven hydrogen generation. - Peuntinger, Katrin; Pilz, T. David; Staehle, Robert; Schaub, Markus; Kaufhold, Simon; Petermann, Lydia; Wunderlin, Markus; Goerls, Helmar; Heinemann, Frank Wilhelm; Li, Jing; Drewello, Thomas; Vos, Johannes G.; et al. (Dalton Transactions, 2014)
Novel photocatalysts based on ruthenium complexes with NHC (N-heterocyclic carbene)-type bridging ligands have been prepared and structurally and photophysically characterised. The identity of the NHC-unit of the bridging ligand was established unambiguously by means of X-ray structural analysis of a heterodinuclear ruthenium-silver complex. The photophysical data indicate ultrafast intersystem crossing into an emissive and a non-emissive triplet excited state after excitation of the ruthenium centre. Exceptionally high luminescence quantum yields of up to 39% and long lifetimes of up to 2 μs are some of the triplet excited state characteristics. Preliminary studies into the visible light driven photocatalytic hydrogen formation show no induction phase and constant turnover frequencies that are independent on the concentration of the photocatalyst. In conclusion this supports the notion of a stable assembly under photocatalytic conditions.

Efficient Access to 5-Bromo- and 5,6-Dibromophenanthroline Ligands - Stumper, Anne; Pilz, Thomas David; Schaub, Markus; Goerls, Helmar; Sorsche, Dieter; Peuntinger, Katrin; Guldi, Dirk Michael; Rau, Sven (European Journal of Inorganic Chemistry, 2017)
Bromo-functionalized precursor molecules are essential for generating desired target compounds through cross-coupling reactions. Herein we show an improved synthetic route, feasible at low temperatures and affording high yields, to the ligands 5-bromo-1,10-phenanthroline (1) and 5,6-dibromo-1,10-phenanthroline (2). The corresponding ruthenium complexes, containing various equivalents of ligand 2, are easily accessible in high yields, including the analogue of tris-homoleptic [Ru(bpy)3]2+ (bpy = 2,2′-bipyridine), [Ru(2)3]2+. X-ray diffraction analyses have provided detailed information on the structures of the ligands and their corresponding metal complexes. An investigation of the electrochemical properties has provided detailed information on the 3MLCT state localized on 2. We show the conversion of heteroleptic ruthenium complexes of these ligands in Suzuki cross-coupling reactions whereas the ligands did not undergo reaction under the same conditions.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Bromine; Cross-coupling; N ligands; Ruthenium; Synthesis design

Photoinduced charge transfer in porphyrin-cobaloxime and corrole-cobaloxime hybrids - Peuntinger, Katrin; Lazarides, Theodore; Dafnomili, Dimitra; Charalambidis, Georgios; Landrou, Georgios; Kahnt, Axel; Sabatini, Randy Pat; Mccamant, David W.; Gryko, Daniel T.; Coutsolelos, Athanassios G.; Guldi, Dirk Michael (Journal of Physical Chemistry C, 2013)
We report on the synthesis of hybrid molecules consisting of a porphyrin or corrole chromophore axially coordinated to a [Co(dmgH) (Cl)] (dmg = dimethylglyoxime) unit via a pyridine group as potential hydrogen forming entities in HO/THF medium. Photophysical, electrochemical, and pulse radiolysis studies on the hybrids and/or their separate components show that selective excitation of the porphyrin or corrole chromophore in its first singlet excited state leads to fast charge separation due to chromophore to cobalt electron transfer. However, this charge separation is followed by even faster charge recombination thereby preventing the accumulation of a reduced cobalt species which would lead to hydrogen production. It is important, nevertheless, that addition of a sacrificial electron donor slows the charge recombination down. In light of the latter it comes as hardly surprising that the photocatalysis experiments in the presence of a sacrificial electron donor (i.e., triethylamine) show modest rates of hydrogen production. © 2012 American Chemical Society.

Polyoxometalate W18O56XO6 clusters with embedded redox-active main-group templates as localized inner-cluster radicals - Vila-Nadal, Laia; Peuntinger, Katrin; Busche, Christoph; Yan, Jun; Lüders, Daniela; Long, De-Liang; Poblet, Josep M.; Guldi, Dirk Michael; Cronin, Leroy (Angewandte Chemie International Edition, 2013)
Non-mixed-valent reduced polyoxometalates, namely WO XO Dawson-like clusters (X=I or Te ) with a localized redox active template have been synthesized and redox properties compared with the pure tungsten control (that is, X=W ). Upon one-electron reduction, the electron localizes on the main-group element, giving I or Te, respectively. These clusters have potential as a new type of electron-transfer reagent. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Solution and solid-state interactions in a supramolecular ruthenium photosensitizer-polyoxometalate aggregate - Heußner, Kirsten; Peuntinger, Katrin; Rockstroh, Nils; Nye, Leanne; Ivanovic-Burmazovic, Ivana; Rau, Sven; Streb, Carsten (Chemical Communications, 2011)
The intermolecular interactions between a ruthenium-based photosensitizer ([Ru(tbbpy)(biH)]) and a molecular metal oxide ([β-MoO]) are investigated in solution and in the solid state. The supramolecular interactions were studied using H-NMR, UV-Vis and emission spectroscopy, ESI mass spectrometry and single-crystal X-ray diffraction. The formation of supramolecular aggregates was observed both in the crystal lattice and in solution. In addition, it is shown that aggregation in solution can be controlled by the competitive formation of ion pairs. © 2011 The Royal Society of Chemistry.

Structural properties of ruthenium biimidazole complexes determining the stability of their supramolecular aggregates - Rockstroh, Nils; Peuntinger, Katrin; Görls, Helmar; Guldi, Dirk Michael; Heinemann, Frank Wilhelm; Schäfer, Bernhard; Rau, Sven (Zeitschrift für Naturforschung Section B-A Journal of Chemical Sciences, 2010)
The results of a detailed investigation of the influence of substituents in a variety of ruthenium biimidazole-type complexes [Ru(R-bpy)2(Ŕ-bi(bz) imH)] (R = H, Bu; Ŕ = H, Me; bi(bz)imH = 2,2-bi(benz)imidazole) on selected structural and photophysical properties is reported. The photo-physical properties are only marginally influenced by the substituents at the bipyridine and the bi-imidazole core. All complexes show intense absorptions in the visible range of the spectrum with maxima around 475 nm, and emission from the formed excited state occurs at wavelengths between 650 and 670 nm. The comparison of structural properties determined by X-ray analysis within a series of related complexes shows that the Ru-N bond lengths to the coordinated bipyridines are not significantly influenced by the substituents, but slight differences in the Ru-N bond lengths to the biimidazole-type ligands can be detected. The reactions between ruthenium complexes containing different biimidazole-type ligands with the sulfate dianion, however, show a strong correlation between the substituents at the biimidazole core and the solubility of the product. The bibenzimidazole-containing complexes precipitate from aqueous solution whereas the ruthenium complex containing unsubstituted biimidazole stays in solution. The solid-state structure of one example of the sulfate-containing products (2b) shows that strong hydrogen bonds between the secondary amine function of the bibenzimidazole and the oxygen functionalities of the sulfate contribute to this unexpected behavior. © 2010 Verlag der Zeitschrift für Naturforschung, Tubingen.

Supramolecular assembly of multicomponent photoactive systems via cooperatively coupled equilibria - Garcia-Iglesias, Miguel; Peuntinger, Katrin; Kahnt, Axel; Krausmann, Jan; Vazquez, Purificacion; Gonzalez-Rodriguez, David; Guldi, Dirk Michael; Torres, Tomas (Journal of the American Chemical Society, 2013)
Here, we show that the synergistic interplay between two binding equilibria, acting at different sites of a (Zn)phthalocyanine-amidine molecule (Pc1), enables the dissociation of the photoinactive phthalocyanine dimer (Pc1) into a three-component system, in which a sequence of light harvesting, charge separation, and charge shift is successfully proven. The aforementioned dimer is assembled by dual amidine-Zn(II) coordination between neighboring Pc1 molecules and gives rise to high association constants (K ≈ 10 M). Such extraordinary stability hampers the individual binding of either carboxylic acid ligands through the amidine group or pyridine-type ligands through the Zn(II) metal atom to (Pc1). However, the combined addition of both ligands, which cooperatively bind to different sites of Pc1 through distinct noncovalent interactions, efficiently shifts the overall equilibrium toward a photoactive tricomponent species. In particular, when a fullerene-carboxylic acid (C A) and either a dimethylamino-pyridine (DMAP) or a phenothiazine-pyridine ligand (PTZP) are simultaneously present, the photoactivity is turned on and evidence is given for an electron transfer from photoexcited Pc1 to the electron-accepting CA that affords the DMAP-Pc1-CA or PTZP-Pc1 -CA radical ion pair states. Only in the latter case does a cascade of photoinduced electron transfer processes afford the PTZP-Pc1-CA radical ion pair state. The latter is formed via a thermodynamically driven charge shift evolving from PTZP-Pc1- CA and exhibits lifetimes that are notably longer than those of DMAP-Pc1-CA. © 2013 American Chemical Society.

Synthesis and Characterization of a Trisheteroleptic Ru-II-Based Molecular Switch - Monczak, Katharina; Peuntinger, Katrin; Sorsche, Dieter; Heinemann, Frank Wilhelm; Guldi, Dirk Michael; Rau, Sven (Chemistry - A European Journal, 2014)
The synthesis of a trisheteroleptic ruthenium complex [Ru(tb)(dppz)(tmbiH(2))][PF6](2) (tb = 4,4'-di-tert-butyl-2,2'-bipyridine, dppz = dipyrido[3,2-a:2',3'-c]phenazin, tmbiH(2) = 5,6,5',6'-tetramethyl-2,2'-bibenzimidazole) is described. In addition, the structural characterisation by means of 1D, 2D H-1 NMR spectroscopy, and mass spectrometry, along with determination of the solid-state structure of the important precursor Ru(tb)(dppz) Cl-2, supports the proposed octahedral coordination geometry. The capability of tmbiH(2) to form hydrogen bonds is corroborated by the solid-state structure. The photochemical characteristics of this complex can be described as a combination of the "light switch" effects, which are either attributed to the dppz or to the tmbiH(2) ligand. To illustrate the molecule's double switchable features, steady-state absorption and emission measurements were performed, which include the determination of the quantum yield and the pK(a) values of the acidic protons of the tmbiH(2) ligand. Notably, the emission lifetimes are sensitive to the solvents used. This phenomenon is due to a proton-coupled deactivation of the excited metal-to-ligand charge transfer (MLCT) state of the complex.
Keywords: bibenzimidazole; light switch effect; molecular switch; pH dependency; trisheteroleptic Ru-II complex

Synthesis and Properties of Acridine and Acridinium Dye Functionalized Bis(terpyridine) Ruthenium(II) Complexes - Eberhard, Jens; Peuntinger, Katrin; Froehlich, Roland; Guldi, Dirk Michael; Mattay, Jochen (European Journal of Organic Chemistry, 2018)
We present first principle studies on the rational design of an acridine/N-methylacridinium dye (Acr/MeAcr+) substituted terpyridine ligand to investigate if these chromophores can act as triplet-energy storage units in bis(terpyridine) ruthenium(II) complexes. We studied the influence of the dye form (Acr/MeAcr+) as well as the interconnecting linker unit (none, 4-phenyl, or 5-thien-2-yl) and investigated these aspects by steady-state/time-resolved spectroscopy, cyclic voltammetry, X-ray structure analysis, and DFT calculations.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Dyes/Pigments; Electronic structure; Energy transfer; Functional organic materials; Ligand design; Ruthenium

Template-Dependent Photochemical Reactivity of Molecular Metal Oxides - Tucher, Johannes; Peuntinger, Katrin; Margraf, Johannes; Clark, Timothy; Guldi, Dirk Michael; Streb, Carsten (Chemistry - A European Journal, 2015)
A combined experimental and theoretical study shows that the photooxidative activity of two isostructural metal oxide clusters depends on their internal templates. To this end, two halide-templated bismuth vanadium oxide clusters [X(Bi(dmso)(3))(2)V12O33](-) (X=Cl-, Br-) are reported and fully characterized. The two clusters show similar absorption features and illustrate that bismuth incorporation results in increased visible-light absorption. Significantly higher photooxidative activity is observed for the bromide-templated cluster compared with the chloride-templated one. Detailed photophysical assays and complementary DFT calculations suggest that the more efficient triplet excited state formation in the Br–containing cluster is the decisive step in the photocatalysis and is due to the heavy-atom effect of the bromide. This concept can therefore open new pathways towards the optimization of photocatalytic activity in metal oxide clusters.
Keywords: density functional calculations; metal oxide; polyoxometalate; self-assembly; template

Tuning of photocatalytic activity by creating a tridentate coordination sphere for palladium - Pfeffer, M. G.; Zedler, L.; Kupfer, Stephan; Paul, M.; Schwalbe, M.; Peuntinger, Katrin; Guldi, Dirk Michael; Guthmuller, J.; Popp, Jürgen; Gräfe, Stefanie; Dietzek, B.; Rau, S. (Dalton Transactions, 2014)
The synthesis and characterisation of an asymmetric potential bridging ligand bmptpphz (bmptpphz = 2,17-bis(4-methoxyphenyl)tetrapyrido[3,2-a:2′, 3′-c:3′′,2′′-h:2′′′, 3′′′-j] phenazine) is presented. This ligand contains a 1,10-phenanthroline (phen) and a 2,9-disubstituted phen sphere and possesses a strong absorbance in the visible. Facile coordination of the phen sphere to a Ru(tbbpy)2 core leads to Ru(bmptpphz) ([(tbbpy) 2Ru(bmptpphz)](PF6)2; tbbpy = 4,4′-di-tert-butyl-2,2′-bipyridine). UV-vis, emission, resonance Raman and theoretical investigations show that this complex possesses all properties associated with a Ru(tpphz) ([(tbbpy)2Ru(tpphz)](PF 6)2; tpphz = tetrapyrido[3,2-a:2′,3′-c: 3′′,2′′-h:2′′′,3′′′- j] phenazine) moiety and that the ligand based absorbances in the vis-part also populate an MLCT like state. The coordination of a Pd-core in the new 2,9-disubstituted phen sphere is possible, leading to a cyclometallation. The tridentate complexation leads to changes in the UV-vis and emission behaviour. Furthermore, the stability of the Pd-coordination is significantly enhanced if compared to the unsubstituted Ru(tpphz). Ru(bmptpphz)PdCl proved to be an active photocatalyst for H2 evolution, albeit with lower activity than the mother compound Ru(tpphz)PdCl2. This journal is © the Partner Organisations 2014.
CRIS-Team Scopus Importer:2023-03-07